Calculation of heat transfer coefficient distribution on 3D geometries from transient liquid crystal experiments - Ryley, J; McGilvray, M; Gillespie, D (American Society of Mechanical Engineers, 2014)
A valuable new technique to provide spatially resolved heat transfer coefficient (HTC) measurements over geometrically complex surfaces has been developed. The method is generally applicable, for use with conventional transient liquid crystal experiments, and uses the capability of commercially available finite element analysis (FEA) software. This technique has many potential applications where lateral conduction effects are significant, and can provide measurements in areas where data have not previously been possible. In the current study it has been applied to a section of a stationary internal cooling passage containing engine realistic features. The technique couples experimental data from transient liquid experiments and FEA, in an iterative procedure, to generate the solutions. Spatially resolved maps of heat transfer have been determined over the surface of the ribs for five Reynolds number conditions (18,000–105,000) for two aspect ratio passages, 1:2 and 1:3. The results are compared to conventionally processed experimental and numerical data. Where the 1D application is applicable results agree within experimental uncertainty (∼6%) at the majority of locations. Typical 1D based methods are unable to provide reliable spatial measurements over ribbed surfaces and to the authors best knowledge this is the first time distributions of HTC have been reported for engine representative rib geometry.